Glucose Availability Alters Gene and Protein Expression of Several Newly Classified and Putative Solute Carriers in Mice Cortex Cell Culture and D. melanogaster - Ceder, Mikaela M.; Lekholm, Emilia; Klaesson, Axel; Tripathi, Rekha; Schweizer, Nadine; Weldai, Lydia; Patil, Sourabh; Fredriksson, Robert (Frontiers in Cell and Developmental Biology, 2020)
Many newly identified SLCs and putative transporters have the possibility to be intricately involved in glucose metabolism. Here we show that many transporters of this type display a high degree of regulation at both mRNA and protein level following no or low glucose availability in mouse cortex cultures. We show that this is also the case in D. melanogaster subjected to starvation or diets with different sugar content. Interestingly, re-introduction of glucose to media, or refeeding flies, normalized the gene expression of a number of the targets, indicating a fast and highly dynamic control. Our findings demonstrate high conservation of these transporters and how dependent both cell cultures and organisms are on transporter proteins during metabolic fluctuations. Several genes were regulated simultaneously to initiate alternative metabolic pathways as a response to low glucose levels to promote cell survival, both in the cell cultures and in the D. melanogaster. Our results establish that newly identified SLCs of MFS type, as well as the putative transporters included in our study, are regulated by glucose availability and are most likely vital for several cellular aspects dependent of glucose and/or its metabolites. Recently, a correlation between dysregulation of glucose in the CNS and numerous diseases such as obesity, type 2 diabetes mellitus as well as neurological disease such as Alzheimer’s and Parkinson’s diseases indicate a complex regulation and fine tuning of glucose levels in the brain. The fact that almost one third of transporters and transporter-related proteins remain orphans with unknown or contradictive substrate profile, location and function, establishes the need for further research about them to fully understand their mechanistic role and their impact on cellular conditions.